Pragmatic Ambiguity in Selected Newspaper Headlines - Dr. Israa Talib Saad (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Ambiguity in language is a quality that makes written or spoken texts open to a number of interpretations. It can be found everywhere. One of the common places where ambiguity can be found is in newspaper headlines. This study examines pragmatic ambiguity in headlines chosen from an issue of the New York Times published in May,2022. The chosen headlines address various fields (business, travel, art, world, real estate and sport). The study aims to investigate why newspaper editors use ambiguous constructions in writing news headlines and how this ambiguity may be solved to convey not only the actual meaning but also what lies beneath what is written. The study analyzes the chosen headlines pragmatically by means of Yule’s model of presupposition (1996). This research is divided into three sections. The first section, which is the introductory, sheds light on the problem of this research, aims, procedures, hypotheses, and limits. The second section is the theoretical background, where a survey has been presented including the discussion of the concept of ambiguity in general and in newspapers in specific with reference to its types. Besides, a separate section is devoted to dealing with pragmatics as the analyses presented based on presupposition, which in turn has been illustrated to clarify the main parts of the model used to analyze the selected headlines in an attempt to solve the ambiguity used in their formulation. The third section presents the methodology and analysis of the chosen headlines to find out the reasons lying behind using ambiguous constructions by news editors, and then present some suggestions for readers in an attempt to enable them understand what lies behind what is written or stated. The analysis is qualitative as a comprehensive description has been presented for the headlines: their illustrations and analyses. The analyses have revealed that existential presupposition as a pragmatic strategy constitutes the most frequent type of presupposition that has been applied, followed by structural presupposition then lexical presupposition. It has also been found out that newspaper editors use ambiguous constructions intentionally to convey meaning beyond the literal meaning expressed by the apparent words, enrich headlines with different structures which suggest additional information or insinuate subtle messages without explicitly stating them.